Eccentric Rotor Drop Dynamics Study of Vertical Maglev Bearing System - Xiaoxu Pang; Dingkang Zhu; Ming Qiu; Dongfeng Wang; Xinlong Wang (Lubricants, 2023)
When considering the problem of a vertical magnetic levitation bearing system, the rotor eccentric fall is more likely to cause the failure of the protective bearing. In this paper, a rotor drop collision model and a protective bearing dynamics model are constructed. It compares and analyzes the evolution of collision force values of the rotor eccentric drop as well as the non-eccentric drop. Further, this paper discusses the law of influence of three factors, rotor quality, rotational speed, and axial protection clearance, on the collision characteristics of the protected bearing in eccentric and non-eccentric cases. It has also experimentally verified this characteristic of rotor speed. The results show that compared with the non-eccentric condition, the axial impact force and radial impact forces of the rotor in the eccentric condition increase by 14% and 114%, respectively. Compared with the non-eccentric condition, with the increase in rotor quality, the axial and radial impact force increase by 68% on average, and the axial depth amplitude of the rotor increases by 350%. With the increase of rotor speed, the axial impact force without an eccentric drop is basically unchanged; the axial impact force of an eccentric drop increases slightly, and the radial impact force increases by 110%. With the increase of axial protection clearance, the radial displacement vibration of the rotor axis increases; the average increase of the maximum axial force is 120 N, and the average increase of the maximum radial force is 100%.